Recessive epidermolytic ichthyosis results from loss of keratin 10 expression, regardless of the mutation location. (26th December 2017) - Vodo, D.; Sarig, O.; Peled, A.; Samuelov, L.; Malchin, N.; Grafi‐Cohen, M.; Sprecher, E.
Summary: Epidermolytic ichthyosis (EI) is a rare skin disorder caused by mutations in the genes KRT1 and KRT10, and is usually inherited in an autosomal dominant fashion. Only five recessive mutations causing EI have been described, all of which are located in the central region of the KRT10 gene. In the current study, we aimed to identify the genetic defect underlying EI in a 12‐year‐old patient. Direct sequencing of the patient's genomic DNA revealed a novel homozygous nonsense mutation residing within the proximal part KRT10 first exon. The mutation was found to co‐segregate with the disease phenotype in an autosomal recessive fashion. Using real‐time quantitative PCR, we found an almost two‐fold decrease in KRT10 expression in the patient's skin compared with the skin of healthy controls. Western blot analysis showed complete absence of keratin 10 protein in the patient's skin, suggesting early protein degradation.